RANCANG BANGUN SISTEM INFORMASI PENENTUAN KEBUTUHAN PENEMPATAN GURU PADA SEKOLAH DASAR BERDASAR PERATURAN BERSAMA LIMA MENTERI - Widiyanto, Adhi; Dewiyani, M.j.; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Education Department Bondowoso District field of education personnel have a duty to analyze of teachers placed needs. This time the field of education personel have a problem to implement analysis of needs teacher placement process among others the length of the process of data collection, and data analysis is still using the manual method. This problem resulted teacher placement needs analysis process takes a long time and error prone. To answer these problems then made an application determining teacher placement needs. Applications made under regulation with five ministers, this application will generate data that shortage or excess school teacher and produce recommendations that can be moved assign teachers. At this stage of the implementation of the application needs analysis the placement of the teachers in primary schools shows conformity with the expectation of 100% and worth to be used. Teacher placement needs analysis process done more effectively and efficiently than ever before. The data used was school data in the academic year 2013 - 2014